2015
DOI: 10.1080/09500693.2015.1072290
|View full text |Cite
|
Sign up to set email alerts
|

The Intellectual Demands of the Intended Primary Science Curriculum in Korea and Singapore: An analysis based on revised Bloom's taxonomy

Abstract: While there has been a remarkable worldwide convergence in the emphases of primary science curricula over the last four decades, the cognitive and knowledge demands that they make on learners have not been well-researched. Without knowing what these intellectual or epistemic requirements are when learning science in school, issues concerning curricular alignment and access to abstract disciplinary knowledge are also likely to occur. To highlight the value of such forms of analyses, we examine the intended prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…This situation shows that the 5 th grade science learning outcomes were given more emphasis on the lower levels than the upper-level cognitive process dimension. The results of this study show similarities with the studies of Lee, Kim, and Yoon (2015), and Mosallanejad (2008). Although learning-centered teaching systems, it is stated that the majority of the learning outcomes are at the level of understanding in Korea and Singapore science curriculums.…”
Section: Resultssupporting
confidence: 90%
“…This situation shows that the 5 th grade science learning outcomes were given more emphasis on the lower levels than the upper-level cognitive process dimension. The results of this study show similarities with the studies of Lee, Kim, and Yoon (2015), and Mosallanejad (2008). Although learning-centered teaching systems, it is stated that the majority of the learning outcomes are at the level of understanding in Korea and Singapore science curriculums.…”
Section: Resultssupporting
confidence: 90%
“…Bloom's taxonomy has served as the basis of many curricula, including those of elementary school mathematics, and has driven the inclusion of tasks of different cognitive levels (Lee et al, 2015). The underlying assumption is that different mathematical tasks may yield different types of students' learning (Doyle, 1988;Hiebert & Wearne, 1993).…”
Section: Thinking Levels Of Mathematical Tasksmentioning
confidence: 99%
“…To determine this, for example, for a curriculum, Stanny (2016) suggested that Revised Bloom Taxonomy (here after RBT) is effective in classifying thinking skills in a hierarchy that ranges from lower level cognitive skills through higher order cognitive skills. Lee et al (2015) examined the primary science curricula used in Korea and Singapore using RBT to find out the general features of the cognitive demands and levels of knowledge required from learners. In their article, the researchers provided useful insights into the complexities of the science curriculum with the results between two similar yet different educational systems.…”
Section: An Overview Of the Education System In Turkeymentioning
confidence: 99%